the Calculation of gaseous storage and Building A 3D Geological model for Jeribe Formation in Mansuriya gas field in Diyala governorate - Mohamed Musadiq Hadi; Salah Ali Hussain (Academic Science Journal)
Al-Mansuriya gas field is considered one of the important gas fields in Iraq because of its good economic gas reserves, The major gas reserves of the Mansuriya field are situated in the Jeribe formation, The period of formation deposition dates back to the lower middle Miocene. The present study aims to build the three-dimensional geological model for Jeribe Formation in Mansuriya Gas Field using (Petrel) software. Drawing on well logs exported from Techlog software in LAS format. Four wells have been chosen in the mansuriya gas field (MN_1, MN_2, MN_3, MN_4) to construct Structural and petrophysical (effective porosity, water saturation and lithology) models. After creating zones for Jeribe   Formation, which was divided into 7 zones J1, J2, J3, J4, J5, J6 and J7  zone, Based on the final results of computer processing interpretation CPI was imported from techlog software. The three-dimensional grid of the Jeribe Formation model that was built consists of (10494848) cell and each cell have dimensions    I =272 * J = 371 * K =104. Petrophysical models (effective porosity, water saturation and lithology) had been constructed for each zone of the Jeribe Formation showing the J2, J3, J4 and J5 are important reservoir units in terms of their good properties (high effective porosity, low water saturation) and Two types of lithology appear (dolomite and limestone) in different proportions to each unit. The results showed that Units J1 and J6 are non-reservoir units that do not contain gas because they consist of layers of anhydrite with very low porosity. The mn-4 well showed different results from the rest of the wells, and none of its units can’t be considered a reservoir due to the large water saturation volume.